Removal of Ammonium Ions from Wastewater Using Natural Zeolites - Ghan, S.D.; Bakshi, H.V.; Bhoskar, B.T. (Asian Journal of Chemistry, 2016)
A few varieties of zeolite crystals, viz., heulandite, clinoptilolite, stilbite, natrolite and scolecite, were collected from different localities of Marathwada region of India. Each zeolite variety was treated with a domestic wastewater sample. In each case ppm level of NH4+ ions of pre-treated and post-treated liquid was determined. It has been found that clinoptilolite and heulandite exhibit a high potential for the removal of ammonium ions from wastewater.